CRYSTAL STRUCTURE, AND HIRSHFELD SURFACE ANALYSIS OF A POLYMERIC Mn(II)COMPLEX WITH 4-AMINOBENZOIC ACID ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Para-aminobenzoic acid (PABA) has garnered significant interest in coordination chemistry due to its ability to form stable complexes with various metal ions. Among these, manganese (Mn) stands out as a versatile metal that can adopt multiple oxidation states and coordination geometries, making it an attractive candidate for synthesizing novel polymeric structures.